Sexual and Relationship Violence Prevention and Response: What Drives the Commuter Campus Student Experience? - Casey, Erin A. (Journal of interpersonal violence, 2021)
This exploratory study brings together two lines of inquiry on (a) college campus-based responses to sexual and intimate partner violence among students, and (b) the characteristics, experiences, and challenges unique to commuter students and commuter institutions of higher education. Using qualitative analysis of 14 in-depth interviews with campus personnel and focus groups with a total of 71 students on three commuter campuses in the Pacific Northwest, we offer a detailed description of the experiences and characteristics of commuter students as they pertain to sexual and relationship violence programming and prevention, the associated nature of commuter campus communities, and the resulting lack of visibility of the issue of sexual and relationship violence on commuter campuses. We conclude that creative, tailored approaches to prevention and response services on commuter campuses are needed to address the unique circumstances and challenges facing commuter campus students.